2017
DOI: 10.2217/fmb-2017-0145
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy in the Diagnosis of HPV DNA in Breast Lesions

Abstract: Aim: HPV DNA has never been investigated in nipple discharges (ND) and serum-derived extracellular vesicles, although its presence has been reported in ductal lavage fluids and blood specimens. Materials & methods: We analyzed 50 ND, 22 serum-derived extracellular vesicles as well as 51 pathologic breast tissues for the presence of 16 HPV DNA types. Results: We show that the presence of HPV DNA in the ND is predictive of HPV DNA-positive breast lesions and that HPV DNA is more represented in intraductal papill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…At this regard, some authors reported circulating HPV DNA in the serum of patients with HPV-associated invasive cancer (10) and as marker for disease extent and recurrence (14). We also found HPV DNA in the serum derived-extracellular vesicles (EVs) of breast pathologies affected women as well as in patient with HPV DNA positive squamous cell carcinoma of the middle rectum (15, 16). EVs are a heterogeneous population of vesicles, which includes exosomes, microvesicles, and apoptotic bodies that differ in size and biophysical properties (17).…”
Section: Introductionmentioning
confidence: 73%
“…At this regard, some authors reported circulating HPV DNA in the serum of patients with HPV-associated invasive cancer (10) and as marker for disease extent and recurrence (14). We also found HPV DNA in the serum derived-extracellular vesicles (EVs) of breast pathologies affected women as well as in patient with HPV DNA positive squamous cell carcinoma of the middle rectum (15, 16). EVs are a heterogeneous population of vesicles, which includes exosomes, microvesicles, and apoptotic bodies that differ in size and biophysical properties (17).…”
Section: Introductionmentioning
confidence: 73%
“…To investigate the HPV type distribution in patients with OPMD and OC, a high-throughput MALDI-TOF mass spectrometry-based method (Mass Array Platform, Agena Bioscience, Hamburg, Germany) was used, as previously described [18]. This method is able to detect 16 HPV DNA types (HPV16, 18,31,33,35,39,45,51,52,53,56,58,59, 66, 68 and 73) in a single well.…”
Section: Low and High-risk Hpv Dna Genotypingmentioning
confidence: 99%
“…Previous studies on cervical, oropharingeal, and breast diseases demonstrated the presence of circulating HPV DNA in the blood of affected patients (8, 3235). Accordingly, we searched HPV DNA also in the blood of our patient.…”
Section: Discussionmentioning
confidence: 97%
“…Tumor-derived exosomes and extracellular vesicles are garnering increasing attention because of their ability to transfer bioactive molecules (mRNAs, microRNAs, DNA, and proteins) between neighboring cancerous or normal cells, and to contribute to human cancer progression. Moreover, exosomes and extracellular vesicles have been implicated in HPV transmission and carcinogenesis (7), and the presence of HPV DNA in the serum derived extracellular vesicles (EVs) of patients with breast diseases has been recently reported (8).…”
Section: Introductionmentioning
confidence: 99%